(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
According to recent revisions to self-control theory, influencing variables (bonds) equivalentto self-control in determining whether or not to participate in deviant conduct. Hirschi maintained that,rather than a cognitive scale or a tally of prior actions, self-control should be operationalized as thequantity and importance of an individual’s social relationships, as proposed by the original theory. Theinfluence of cognitive self-control, as well as attitudinal self-control, is examined in this article , whichadds to the control theory literature. The NYSFS Waves 10 and 11 data were evaluated. Although thefindings imply that both new and old types of self-control are equally predictive of criminality, it isunclear that they are capturing the same phenomena throughout maturity. Control theory implications arepresented.